ONTARIO AUTO INSURANCE REFORM: A GAME OF “WHACK-A-MOLE” - Kelly, Mary; Kleffner, Anne; Tennyson, Sharon (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2015)
Reform of Ontario’s partial no-fault auto insurance product has occurred multiple times since its introduction in 1990. The objectives of these reforms have been to improve affordability and accessibility, with some reforms targeting the product itself and others focused on improving the claims process. This article provides a review of the reforms, their expected outcomes, and the actual impact on losses and premiums. Overall we find that the success of each reform has been short-lived, and by 2014 the average combined first-party and third-party personal injury loss per vehicle was 50 percent higher in real terms than in 1991. Further examination reveals that the Greater Toronto Area (GTA) is responsible for most of the claims growth over this time period, while there has only been marginal growth in both claim frequency and severity in other parts of the province. The presence of generous benefits in the absence of controls to mitigate moral hazard appear to have led to excessive and abusive claiming behaviours on the part of both claimants and medical providers, contributing to the explosion in loss costs in the GTA.